2016
DOI: 10.1074/jbc.r116.746032
|View full text |Cite
|
Sign up to set email alerts
|

A Greek Tragedy: The Growing Complexity of Alzheimer Amyloid Precursor Protein Proteolysis

Abstract: Proteolysis of the amyloid precursor protein (APP) liberates various fragments including the proposed initiator of Alzheimer disease-associated dysfunctions, amyloid-␤. However, recent evidence suggests that the accepted view of APP proteolysis by the canonical ␣-, ␤-, and ␥-secretases is simplistic, with the discovery of a number of novel APP secretases (including ␦-and -secretases, alternative ␤-secretases) and additional metabolites, some of which may also cause synaptic dysfunction. Furthermore, various pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
122
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(127 citation statements)
references
References 101 publications
0
122
0
1
Order By: Relevance
“…Alternative cleavage of APP by α-secretase (ADAM-10) prevents the formation of Aβ and sets the basis for the non-amyloidogenic pathway (Kuhn et al, 2010). While α-, β- and γ-secretases constitute the classical enzymatic backbone of APP processing, alternative APP processing enzymes are being discovered, including δ- and η-secretases (Andrew et al, 2016). Early work in cultured HEK cells showed that some membrane-type matrix metalloproteinases (MT-MMPs) cleave APP at several sites of the ectodomain (Ahmad et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Alternative cleavage of APP by α-secretase (ADAM-10) prevents the formation of Aβ and sets the basis for the non-amyloidogenic pathway (Kuhn et al, 2010). While α-, β- and γ-secretases constitute the classical enzymatic backbone of APP processing, alternative APP processing enzymes are being discovered, including δ- and η-secretases (Andrew et al, 2016). Early work in cultured HEK cells showed that some membrane-type matrix metalloproteinases (MT-MMPs) cleave APP at several sites of the ectodomain (Ahmad et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…5 ). Thereby, concerted cleavage of β-secretase and α-secretase result in the secretion of sAPPβ and shorter Aβ peptides 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The traditional view that concerted processing of APP by the α, β and ɣ secretases produces Aβ amyloidogenic and non-amyloidogenic peptides is complicated by the recognition of alternative APP cleavage sites [170]. Some elongated Aβ-related peptides have been isolated and rigorously characterized by amino acid sequencing.…”
Section: The Complicated Catalog Of App/aβ-related Peptides and Ad Ammentioning
confidence: 99%